2018
DOI: 10.7554/elife.37090
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated culturing, modeling and transcriptomics uncovers complex interactions and emergent behavior in a three-species synthetic gut community

Abstract: The composition of the human gut microbiome is well resolved, but predictive understanding of its dynamics is still lacking. Here, we followed a bottom-up strategy to explore human gut community dynamics: we established a synthetic community composed of three representative human gut isolates (Roseburia intestinalis L1-82, Faecalibacterium prausnitzii A2-165 and Blautia hydrogenotrophica S5a33) and explored their interactions under well-controlled conditions in vitro. Systematic mono- and pair-wise fermentatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 77 publications
(107 reference statements)
1
97
0
Order By: Relevance
“…RNAseq thus confirmed that there is an emergent behavior in the co-cultures and that the observed changes were not just due to variations in inoculum composition or the lag phase 67 . Taken together, our integrated modeling, co-culturing and transcriptomics approach provided mechanistic insights into the observed increase in cholera infection severity in dual infections with ETEC where ETEC co-infection results in an increased growth of V. cholerae due to expanded metabolic capabilities enabled by ETEC.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…RNAseq thus confirmed that there is an emergent behavior in the co-cultures and that the observed changes were not just due to variations in inoculum composition or the lag phase 67 . Taken together, our integrated modeling, co-culturing and transcriptomics approach provided mechanistic insights into the observed increase in cholera infection severity in dual infections with ETEC where ETEC co-infection results in an increased growth of V. cholerae due to expanded metabolic capabilities enabled by ETEC.…”
Section: Resultsmentioning
confidence: 57%
“…To assess the level of genetic perturbations due to addition of ETEC as an interaction partner to V. cholerae cultures, we conducted a dual RNAseq analysis 64-67 of V. cholerae co-cultures (Figure 1, Step 4) with each of the two ETEC strains (E36 or E616). We then compared the gene expression levels for each pathogen to its single-culture (see methods section and Tables S7-S10 at https://github.com/alyamahmoud/coinfection_modeling/blob/master/supplementary_material/supplementary_tables.xlsx).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible interaction is via predicted production of formate by Tyzzerella , that may be metabolised by Faecalibacterium , as has been described in an in silico biofilm model [42] ( Fig S8) . Delineating intricate and complex cross-feeding relationships is difficult and cannot be predicted from non-community cultures, as strains grow, and behave differently when grown in co-culture, compared to those grown individually [43]. Further studies, possible utilising isotope labelling, would be required for targeted identification of metabolites impacting these important EPS-associated cross-feeding networks [44].…”
Section: Discussionmentioning
confidence: 99%
“…These communities can range from very few species to complex aggregates of trillions of cells and go through stages of community succession (Lyautey et al , 2005; Datta et al , 2016; Wright et al , 2019). The complexity of community dynamics, even in low diverse communities, can be illustrated through the interactions of three common gut bacteria cultivated under well‐controlled in vitro conditions (D'Hoe et al , 2018). The results showed the difficulty in predicting the winner without a predictive model, which should include both the internal metabolism of community members, as well as their response to interaction partners.…”
Section: The Concept and Mechanisms Of Stochasticity In Microbial Ecomentioning
confidence: 99%